REKONTRUKSI FIQH ZAKAT PERHIASAN DALAM PERSPEKTIF QADHI ABU SYUJA‘ AL-ASFAHANI DAN A. HASSAN - Deden Muhammad Jamhur (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2014)
The issue of zakat would be interesting to be discussed. It is not caused by some kind of zakat, but more. In the fact, Muslim could not be separated from zakat. The zakat is a medium to purify himself and his property. Zakat of Jewelry is one of type of zakat, and became an important position in human life. However, there was a difference of opinion among Muslim scholars about the obligation to implement the zakat of jewelry. Qadhi Abu Syuja‘ Al-Asfahani said that zakat of jewelry must not to be implemented, but if we has an excess of jewelry. Whereas A. Hassan, he said that zakat should be accomplished without waiting haul and nishab. Zakat of jewelry is something that was not touched directly by the texts of the Qur'an, but the issue of jewelry zakat lies at a certain hadiths. Qadhi Abu Syuja‘ Al-Asfahani argued based on mawquf hadith from Jabir bin Abdillah. And A. Hassan argued based on the Hadith Shahih. This paper attempts to explain a tought of both scholars about their opinions in implementing of zakat of jawelry.